1985
DOI: 10.1021/np50037a006
|View full text |Cite
|
Sign up to set email alerts
|

The Phenyl- and Biphenyl-Quinolizidines of In-Vitro-Grown Heimia salicifolia

Abstract: Under the conditions delineated in this paper, alkaloid synthesis was not detectable in heterotrophic callus and suspension cultures of Heimia salicifolia. However, in vitro-grown shoots are active in alkaloid biosynthesis, yielding the biphenylquinolizidine lactones vertine (1), lytrine (5), and lyfoline (7), the ester alkaloids demethoxyabresoline (14) and epidemethoxylabresoline (11), the phenylquinolizidinols demethyllasubine-I (10) and demethyllasubine-II (12), and several minor alkaloids that had not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…This has been the subject of careful examina t i ~n . ~~ It was shown first that a mixture of ~-[2,6-~H]tyrosine and ~-[U-'~C]tyrosine was incorporated into (S)-reticuline (29) and (5')-coclaurine (45) in leaves of Annona reticulata. Both alkaloids had similar 3H/14C ratios, which were close to the theoretical value (which shows that L-tyrosine was incorporated in the expected way and without degradation).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This has been the subject of careful examina t i ~n . ~~ It was shown first that a mixture of ~-[2,6-~H]tyrosine and ~-[U-'~C]tyrosine was incorporated into (S)-reticuline (29) and (5')-coclaurine (45) in leaves of Annona reticulata. Both alkaloids had similar 3H/14C ratios, which were close to the theoretical value (which shows that L-tyrosine was incorporated in the expected way and without degradation).…”
mentioning
confidence: 99%
“…Further, it was found that, in A . reticulata, ~-[ring-U-'~C]tyrosine was used, similarly for the two halves of coclaurine (45) and reticuline (29); the ratios were, respectively, 1 :4.9 and 1 :4.7. Thus the two alkaloids must have one and the same biosynthetic origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Su floración es amarilla con dos centímetros de diámetro, formada por seis pétalos en pares a la porción axilar de la hoja y semillas de 0.5mm de diámetro, que en ambientes óptimos su germinación se produce entre los 10 y 16 meses. (Rother, 1985).…”
Section: Introductionunclassified